Enhancing Patronage Intention on Online Fashion Industry in Indonesia: The Role of Value Co-Creation, Brand Image, and E-Service Quality - Tantri Yanuar Rahmat Syah; Dora Olivia (Cogent Business & Management, 2022)
Value co-creation has become an essential strategy in business that encourages customer involvement in creating products that meet customer demands and have superior value. Brand image and e-service quality are still important factors that influence customer decision making in purchasing products online. The purpose of this study is to identify the role of value co-creation, brand image, and e-service quality toward patronage intentions in the online Muslim fashion industry with a moderating effect of religiosity and mediated by customer perceived value and customer satisfaction. This study was designed using a purposive sampling method involving 301 online customers from several Muslim fashion brands in Indonesia. Data were analyzed utilizing Structural Equation Model (SEM) with SmartPLS 3.0. The main point of our findings in this study is that value co-creation, brand image, and e-service quality have an indirect effect on patronage intentions through customer perceived value and customer satisfaction. In contrast, the moderating effect of religiosity has no significant effect on patronage intentions. This research provides academic contributions and adds value to existing theories where value co-creation can be applied online in non-service sectors such as the fashion industry that is not much analyzed. Furthermore, the managerial implication of this research for industrial practitioners is to implement value co-creation within the company, improve the e-service quality, and develop products that have a strong brand image that can increase sales value, leading to the company's competitive advantage.
Keywords: 650; Brand Image; customer perceived value; customer satisfaction; E-service quality; patronage intention; religiosity; Value co-creation